MODERN DEVELOPMENT STRATEGIES FOR REGIONS: TRANSITION FROM CENTRALIZED TO DECENTRALIZED GOVERNANCE - Ісмаілов, Алтан (Journal of Strategic Economic Research, 2024)
The analysis of the transformation processes in approaches to regional development is conducted through a detailed examination of the transition from a traditional centralized management model to progressive decentralization. In the context of contemporary challenges particularly the ongoing war in Ukraine, the possibilities and advantages of decentralization as a means to enhance the efficiency of regional development management are explored. Special attention is paid to analyzing how decentralization can promote the activation of local initiatives, increase community participation in decision-making processes, and attract investments, which collectively can significantly improve conditions for the sustainable development of regions. Studying the experience of decentralization in other countries, as well as adapting best practices to the conditions of Ukraine, is of great importance for developing effective regional development strategies capable of responding to contemporary challenges and contributing to the country's post-war recovery. The hypothesis is that the decentralization of power and the transfer of greater autonomy to the local level under war conditions can facilitate flexible responses to regional challenges, activation of local initiatives, and attraction of investments for the recovery and development of affected regions. The aim of the study is to determine strategies for effective regional development through decentralization mechanisms, considering the challenges posed by military actions in Ukraine. To achieve the set goal, methods of scientific literature analysis, comparative analysis, case studies, and expert evaluation methods were used to study the experience of decentralization in different countries. It has been proven that decentralization contributes to the improvement of management efficiency, activation of local initiatives, and attraction of investments, which is important for the recovery and development of Ukraine's regions in the post-conflict period. It has been proven that decentralization is a key factor in the sustainable development of regions. An important direction for further research is the study of specific mechanisms and tools of decentralization that can be effective in conditions of war and post-conflict recovery. Also relevant is the analysis of the impact of decentralization on attracting investments and developing local communities.